An integrated multiomic and quantitative label-free microscopy-based approach to study pro-fibrotic signalling in ex vivo human precision-cut lung slices - Khan, Muzamil Majid; Poeckel, Daniel; Halavatyi, Aliaksandr; Zukowska-Kasprzyk, Joanna; Stein, Frank; Vappiani, Johanna; Sevin, Daniel C.; Tischer, Christian; Zinn, Nico; Eley, Jessica D.; Gudmann, Natasja Stæhr; Muley, Thomas; et al. (The European respiratory journal, 2021)
Fibrosis can affect any organ, resulting in the loss of tissue architecture and function with often life-threatening consequences. Pathologically, fibrosis is characterised by the expansion of connective tissue due to excessive deposition of extracellular matrix (ECM) proteins, including the fibrillar forms of collagen. A significant limitation for discovering cures for fibrosis is the availability of suitable human models and techniques to quantify mature fibrillar collagen deposition as close as possible to human physiological conditions. - Here we have extensively characterised an ex vivo cultured human lung tissue-derived, precision-cut lung slices (hPCLS) model using label-free second harmonic generation (SHG) light microscopy to quantify fibrillar collagen deposition and mass spectrometry-based techniques to obtain a proteomic and metabolomic fingerprint of hPCLS in ex vivo culture. - We demonstrate that hPCLS are viable and metabolically active, with mesenchymal, epithelial, endothelial and immune cell types surviving for at least 2 weeks in ex vivo culture. Analysis of hPCLS-conditioned supernatants showed a strong induction of pulmonary fibrosis-related ECM proteins upon transforming growth factor-β1 (TGF-β1) stimulation. This upregulation of ECM proteins was not translated into an increased deposition of fibrillar collagen. In support of this observation, we revealed the presence of a pro-ECM degradation activity in our ex vivo cultures of hPCLS, inhibition of which by a metalloproteinase inhibitor resulted in increased collagen deposition in response to TGF-β1 stimulation. - Together the data show that an integrated approach of measuring soluble pro-fibrotic markers alongside quantitative SHG-based analysis of fibrillar collagen is a valuable tool for studying pro-fibrotic signalling and testing anti-fibrotic agents. - Tweetable abstract ERSpublications - click to tweetMultiomic and label-free imaging-based characterisation of ex vivo cultured human precision-cut lung slices (hPCLS) reveals that MMP signalling is a rate-limiting factor necessary for deposition of fibrillar collagen in ECM of hPCLS https://bit.ly/3rcUa0e
Gesehen am 20.09.2021